Forum: Quilting as metaphor for theological education - Park, Sophia S. (Teaching theology and religion, 2019)
How is quilt-making both metaphor and pedagogy for early-career faculty of theology and religion who seek to cultivate critical and creative imagination for teaching, and to probe the challenges and promises of complex identities and vocations within 21st-century landscapes of theological education? This forum presents essays (with explanatory introduction) by five members of the 2016-2017 Workshop for Early Career Theological School Faculty, who were impelled to story their experience of being "handed over to themselves" by an "arts and craft" project which forced them to think with their hands, speak with found objects, and re-present themselves in the form of 12 × 12-inch quilt squares. In self-reflexive prose, these scholar-teachers offer through this medium a glimpse of their unexpected moments of revelatory learning, as each was pulled into deeper contemplation of their personhood, experience, know-how, and practical wisdom, each uncovering valuable hidden sources for more expansive theological query, and each re-thinking the possibilities for theological education and its pedagogies.